INCREASED KNOWLEDGE OF WOMAN ADOLESCENT ABOUT ABORTUS PROVOCATUS CRIMINALIS AFTER IN HEALTH EDUCATION - Fernanda Sharen Maissy Wuisan; Lucia Moningka; Esther N. Tamunu (Jurnal Ilmiah Perawat Manado (Juiperdo), 2018)
Background: Abortion provocateurs criminalis is an abortion that occurs due to actions that are not legal or not based on medical indications. The incidence of abortion in Indonesia according to the BKKBN every year there is an increase of about 15% and of that number 800,000 of them are carried out by young women who are still sitting in school. Data found in SMK Cokroaminoto, Manado City, 5 female students who dropped out of school due to pregnancy out of wedlock and 2 of them took shortcuts by aborting provocateurs criminals. Objective: This study is to determine the effect of health education on the level of knowledge of adolescent girls about abortion provocateurs criminals. Method: The research design used was a pre-experimental method with a one-group pretest-posttest method in which the design features were not compared to a control group. The study population was female teenagers grade X and XI at SMK Cokroaminoto Manado, amounting to 49 people. The sampling technique used was Total Sampling, as many as 31 people. Results: Analysis with the Wilcoxon signed-rank test. The test results have a significant effect on health education about abortion provocateurs criminal on the level of knowledge of young women (α ≤ 0.05 ie p-value = 0,000). Conclusion: Health education about abortion provocatus criminals increases the knowledge of young women. Suggestions are expected that young women can increase awareness to prevent abortion of provocateurs criminalis.